Journalism today - Ferguson, Donald L.; Patten, Jim.; Wilson, Bradley (Lincolnwood, Ill. : National Textbook Co., 2001)
Discusses the history and responsibilities of the Media, the gathering, writing, and presentation of news, and the future of journalism as technology changes.
Includes index.
Keywords: Journalism; Journalism, High school; Journalism